1991
DOI: 10.1109/59.76693
|View full text |Cite
|
Sign up to set email alerts
|

Least median of squares estimation in power systems

Abstract: Static state estimators currently in use in power systems are prone to masking by multiple bad data. This is mainly because the power system regression model contains many leverage points ; typically they have a cluster pattern. As reported recently in the statistical literature, only high breakdown point estimators are robust enough to cope with gross errors corrupting such a model. This paper deals with one such estimator, the least median of squares estimator, developed by Rousseeuw in 1984. The robustness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
66
0
16

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(82 citation statements)
references
References 27 publications
0
66
0
16
Order By: Relevance
“…However, there are some difficulties for practical application. Repeated state and paramete estimation are needed to identify error telemetry and error network parameters, which needs a lot of calculation [7].…”
Section: A Identification Of Suspicious Branch Methods Based On Lagramentioning
confidence: 99%
“…However, there are some difficulties for practical application. Repeated state and paramete estimation are needed to identify error telemetry and error network parameters, which needs a lot of calculation [7].…”
Section: A Identification Of Suspicious Branch Methods Based On Lagramentioning
confidence: 99%
“…Milli et. al, in [14], have applied the LMS estimator on the same system. Physically, the resistance of all lines of the three-bus network are taken to be zero.…”
Section: DC Three Bus Test Systemmentioning
confidence: 99%
“…Chen and Abur have proposed the method of placement of PMUs to enable bad data detection in state estimation [17]. Reference [18] and [19] have devised the concepts of robust distances and influence functions in regression analysis of measurement equations to identify leverage points in a system. But they did not discuss about detecting bad data in leverage data points.…”
mentioning
confidence: 99%
“…It has been reported that there are number of ways one can identify the leverage points from the diagonal elements of the hat matrix, Mahalanobis distance (MD) of measurements, projection statistics (PS) [5], [16], etc. Reference [19] has devised the concept of influence function as a combination of influence of residuals and influence of position in factor space. Thus, looking at the influence function one can identify bad data even for influential measurements.…”
mentioning
confidence: 99%